Evaluation of PaCO2 trend in COVID-19 patients undergoing helmet CPAP in the emergency department - Nicolo Capsoni; Daniele Privitera; Chiara Airoldi; Silvia Gheda; Annamaria Mazzone; Gianluca Terranova; Filippo Galbiati; Andrea Bellone (Emergency Care Journal, 2023)
The use of continuous positive airway pressure (CPAP) in COVID-19 hypoxemic respiratory failure (h-ARF) under a strict protocol has been described to be highly efficient. However, early prediction of failure is crucial to avoid delayed intubation. Lower PaCO2 values may represent a higher inspiratory effort and, therefore, may help identify patients at greatest risk of CPAP failure. Aim of this study was to observe the PaCO2 trend of COVID-19 patients with h-ARF before and after the initial treatment with helmet-CPAP. A case series study was conducted from November 2020 to March 2021. All adult patients with h-ARF secondary to COVID-19 treated with helmet-CPAP and eligible for endotracheal intubation were observed. Of a total of 54 patients, 32 (59.3%) underwent intubation. Seven (12.9%) patients died in the ETI group, and none in the non-ETI group. Median PaO2/FiO2 ratio on admission was 91mmHg [IQR 68-185] vs. 104mmHg [IQR 85-215] (p=0.137) in the ETI e non-ETI group, respectively. No differences were found either for PaCO2 values on admission (31.5mmHg [IQR 27-35] vs. 29.3mmHg [IQR 27.7-40]) and for PaCO2 variations after 120 minutes of CPAP (+2.38mmHg ± 3.65 vs. +2.73mmHg ± 3.96). Changes in PaCO2 values were observed during an initial helmet-CPAP trial, but no differences were found in those undergoing endotracheal intubation as compared to the others.